2019
DOI: 10.1039/c8sc04337j
|View full text |Cite
|
Sign up to set email alerts
|

Simple electrochemical reduction of nitrones to amines

Abstract: Only electricity is needed for the transformation of nitrones to amines. Such a direct double reduction has not been reported by any sole chemical reagent in a single step process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…33 It was suggested that an intermediate benzylic radical was formed by electrochemical reduction of a benzylidene imine and, through examination of a series of controls, that d 6 -DMSO acted as a deuterium source through a deuterium atom transfer (Scheme 8). This is in contrast to a similar study by Rodrigo and Waldvogel, 34 who identified an imine as an intermediate in their electrochemical reduction of nitrones to amines, and proposed a final protonation step in a MeCN/H 2 O solvent (rather than a HAT). Li and Huang here also invoke an oxidation of DMSO to dimethyl sulfone under air; the preference of this over other oxidative processes such as product oxidation to a radical-cation, followed by deprotonation to regenerate the benzylic radical (in a similar fashion to that in Scheme 7b), was indirectly inferred through control reactions where no deuterium incorporation was found when the secondary amine was subjected to similar reaction conditions (Scheme 8b).…”
Section: Carbon-heteroatom P-bondscontrasting
confidence: 99%
“…33 It was suggested that an intermediate benzylic radical was formed by electrochemical reduction of a benzylidene imine and, through examination of a series of controls, that d 6 -DMSO acted as a deuterium source through a deuterium atom transfer (Scheme 8). This is in contrast to a similar study by Rodrigo and Waldvogel, 34 who identified an imine as an intermediate in their electrochemical reduction of nitrones to amines, and proposed a final protonation step in a MeCN/H 2 O solvent (rather than a HAT). Li and Huang here also invoke an oxidation of DMSO to dimethyl sulfone under air; the preference of this over other oxidative processes such as product oxidation to a radical-cation, followed by deprotonation to regenerate the benzylic radical (in a similar fashion to that in Scheme 7b), was indirectly inferred through control reactions where no deuterium incorporation was found when the secondary amine was subjected to similar reaction conditions (Scheme 8b).…”
Section: Carbon-heteroatom P-bondscontrasting
confidence: 99%
“…When a graphite rod was used as the anode, the reaction only gave trance conversion (entry 9). Such an unusual anode effect in a cathodic reduction was also observed recently by Waldvogel and Rodrigo in their work on the electrochemical reduction of nitrones …”
Section: Resultssupporting
confidence: 80%
“…A broad scope of aromatic and heteroaromatic amines, containing a large variety of functional groups, was accessible. The utilization of electric current allowed for the first time the avoidance of two different reagents for this reduction, something mandatory if this transformation were performed with classical chemical reagents …”
Section: Other Functionalitiesmentioning
confidence: 99%